Religious cohesion in times of conflict Christian-Muslim relations in segregated towns - Holden, Andrew (Continuum, 2009)
Andrew Holden presents the results and analysis of the key findings of a sociological investigation which seeks to establish the contribution that Christian-Muslim partnerships can make to community cohesion.